Analisis Anak Berkebutuhan Khusus dengan Kesulitan Belajar (Disleksia) dan Kesulitan Menulis (Disgrafia) pada Siswa Kelas 3 SDN Pondok Bahar 6 Kota Tangerang - Nurfadhillah, Septy; Padyah, Padyah; Khofifaturrahmah, Mia; Nurbaiti, Lita; M, Nanda Oktaviani; A, Amiratul Muzeeb; A, Apik Woro (YASIN, 2021)
This research was conducted at SDN Pondok Bahar 06 with the aim to identify and know the application of curriculum, learning mechanisms., as well as the difficulties of students learning to read (dyslexia) and the difficulties of students learning to write (dysgraphia). The methods used in this study use this type of qualitative research with descriptive methods. Children with learning problems are children who have difficulty in academic tasks, caused by the presence of minimal dysfunction of the brain, or in basic psychological, so that their learning achievement is not in accordance with their actual potential. Children who have learning difficulties, either in general or specifically such as dyslexia and dysgraphia need special educational services in the learning process in school. The results of this study show that the school still uses the 2013 curriculum and still lacks handling for children with special needs dyslexia and dysgraphy. In the learning mechanism in dyslexic and disgrafia children get special services in the form of additional learning outside of general lesson hours. Children with special needs dyslexia and dysgraphia are required.